2019
DOI: 10.1155/2019/5061934
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic and Functional Results following Subtalar Arthroereisis in Pediatric Flexible Flatfoot

Abstract: Introduction. Flexible flatfoot (FFF) is one of the most common skeletal disorders in children. In symptomatic patients who do not respond to conservative measures, surgery may be an option. Subtalar arthroereisis consists of limiting excessive eversion of the subtalar joint through different types of implants. Materials and Methods. We carried out a retrospective study of 16 patients (32 feet) intervened for FFF with a subtalar device (arthroereisis), across the period of 2008-2015 with a minimum follow-up pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 32 publications
1
41
0
Order By: Relevance
“…Fourteen patients had a concomitant spring ligament reconstruction. Ten studies routinely removed implants 16 , 20 , 21 , 23 , 25 30 after a minimum period of 18 months, at skeletal maturity or using the formula: planned removal/months post op = (age in years x 2) plus 6. The average follow-up period was 30.9 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen patients had a concomitant spring ligament reconstruction. Ten studies routinely removed implants 16 , 20 , 21 , 23 , 25 30 after a minimum period of 18 months, at skeletal maturity or using the formula: planned removal/months post op = (age in years x 2) plus 6. The average follow-up period was 30.9 months.…”
Section: Resultsmentioning
confidence: 99%
“… 15 , 33 , 35 Only ten studies measured any form of kinematics 12 , 14 , 15 , 23 26 , 30 , 33 , 35 and only eight studies utilized patient-reported outcomes. 14 16 , 21 23 , 28 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…In 1992, Viladot[ 7 ] reported the success rate achieved by the first non-osseous sinus tarsi implant. The aim of implants is to correct the FFF deformity with preservation of foot function and limitation of excessive anterior displacement of the talus upon the calcaneus[ 8 ]. Moreover, some authors[ 9 , 10 ] have hypothesized that CS could play a role in the activation of mechanoreceptors in the sinus tarsi, although it has not yet been supported by experimental evidence.…”
Section: Introductionmentioning
confidence: 99%
“…After writing emails to corresponding authors, there had been no response until 31 Dec., 2019. We excluded 1 study for screw inserted in talus 6 ; 7 studies for lack of calcaneal pitch angle, Meary’s angle, and AOFAS 7 13 and 6 studies for lack of standard deviation or raw data 14 19 .…”
Section: Resultsmentioning
confidence: 99%